Approaches to Study Gap Junctional Coupling - Stephan, Jonathan; Eitelmann, Sara; Zhou, Min (Frontiers in Cellular Neuroscience, 2021)
Astrocytes and oligodendrocytes are main players in the brain to ensure ion and neurotransmitter homeostasis, metabolic supply, and fast action potential propagation in axons. These functions are fostered by the formation of large syncytia in which mainly astrocytes and oligodendrocytes are directly coupled. Panglial networks constitute on connexin-based gap junctions in the membranes of neighboring cell that allow the passage of ions, metabolites, and currents. However, these networks are not uniform, but exhibit a brain region-dependent heterogeneous connectivity influencing electrical communication and intercellular ion spread. Here, we describe different approaches to analyze gap junctional communication in acute tissue slices that can be implemented easily in most electrophysiology and imaging laboratories. These approaches include paired recordings, determination of syncytial isopotentiality, tracer coupling followed by analysis of network topography, and wide field imaging of ion sensitive dyes. These approaches are capable to reveal cellular heterogeneity causing electrical isolation of functional circuits, reduced ion-transfer between different cell types, and anisotropy of tracer coupling. With a selective or combinatory use of these methods, the results will shed light on cellular properties of glial cells and their contribution to neuronal function.